Overweight and Obesity as Risk Factors of Breast Cancer in Premenopausal and Postmenopausal Women: Meta-Analysis - Fadhila, Shofia Nur; Murti, Bhisma; Widyaningsih, Vitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: A woman has an increased risk of breast cancer due to increased exposure to the hormone estrogen during her life due to early menarche, late menopause, and/or the absence of childbearing. Epidemiological data show that menopausal status has a risk factor for breast cancer. The aim of this study was to investigate overweight and obesity as risk factors for premenopausal and postmenopausal breast cancer. Subjects and Method: A systematic review and meta-analysis study was conducted by systematically reviewing articles published from 2010-2021 in the PubMed, Google Scholar, SpringerLink and Science Direct databases with the keywords overweight AND obesity AND